Dual Lewis site creation for activation of methanol on Fe3O4(111) thin films. Issue 9 (30th January 2020) - Xu, Fang; Chen, Wei; Walenta, Constantin A.; O'Connor, Christopher R.; Friend, Cynthia M.
Abstract : Adjacent oxygen adatoms and lattice iron atoms on magnetite surfaces serve as dual Lewis sites that oxidize methanol to formaldehyde. Abstract : Despite a wide application in heterogeneous catalysis, the surface termination of Fe3 O4 (111) remains controversial. Herein, a surface with both Lewis acid and base sites is created through formation of an Fe3 O4 (111) film on α-Fe2 O3 (0001). The dual functionality is generated from a locally nonuniform surface layer of O adatoms and Fetet1 sites. This reactive layer is reproducibly formed even in oxygen-free environments because of the high mobility of ions in the underlying α-Fe2 O3 (0001). The atomic structure of the Fe3 O4 (111) surface was identified by scanning tunneling microscopy (STM) and density functional theory (DFT) using the registry of the overlayers with the surface and the distinct electronic structure of oxygen adatom (Oad ) and uncovered lattice Fetet1 . The surface is dominated by the interface of Oad and Fetet1, a Lewis acid–base pair, which favors methanol dissociation at room temperature to form methoxy. Methoxy is further oxidized to yield formaldehyde at 700 K in temperature programmed reaction spectra, corresponding to an approximate activation barrier of 179 kJ mol −1 . The surface termination of Fe3 O4 (111) is fully recovered by rapid heating to 720 K in vacuum, demonstrating the high mobility of ions in this material. The work establishes a clear fundamental understanding of a unique magnetite surface and provides insights into the origin of selective oxidation of alcohols on magnetite-terminated catalysts.